Bianchi type-V early-decelerating and late-time-accelerating cosmological model with a perfect fluid and heat conduction - Chandel S.; Ram S. (My University, 2025)
In this paper, we discuss Einstein's field equations for a spatially homogeneous and anisotropic Bianchi type-V space-time in the presence of a perfect fluid and heat conduction. We obtain exact solutions of the field equations by applying the hybrid expansion law for the average scale factor that yields power-law and exponential-law cosmologies in its special cases. We observe that the universe exhibits a transition from deceleration to acceleration in its expansion. The universe is anisotropic at the early stages of its evolution and becomes isotropic at late time. At late time dark energy dominates, leading to accelerated expansion of the universe. The physical and kinematical behaviors of the model are also discussed. © 2015 Published by NRC Research Press.